(untitled) (Scientific journal of the Fergana State University, 2023)
This article depicts the importance of realia in translation. At the same time, the common errors that have been made by some translators in terms of translating as the culture-bound words and the possible ways to prevent them have been raised as a major discussing topic. Successful strategies of translating equivalent lacking words into target language and choosing the properly translated form of word patterns have been also suggested.